Adverse Effects of Hydroxychloroquine in Different Connective Tissue Disorders Used for Dermatological Purpose - Sarwat Abdus Salam, Sarwat Abdus Salam; Talat, Humaira (Indus Journal of Bioscience Research, 2025)
Introduction: Hydroxychloroquine (HCQ) is one of the most frequently used drugs in dermatology with a wide variety of uses. This study was conducted to determine adverse effects of HCQ when given in patients of auto immune disorders. Objectives: To determine frequency of adverse effects of hydroxychloroquine in all patients using hydroxychloroquine for different connective tissue disorders used for dermatological purpose. Study design and setting: Cross sectional study was conducted at the Department of Dermatology, Civil Hospital Karachi during the period from July 9, 2024 to January 8, 2025. Methodology: Patients aged 12 to 70 years of both genders already diagnosed cases of connective tissue disorder taking hydroxychloroquine for more than 3 months visiting derma OPD for follow-up check-up were enrolled using non-probability consecutive sampling technique. Study was conducted after approval of hospital ethical committee and written informed consent of patients. Demographic data was noted. Adverse effects of hydroxychloroquine were noted. Data was entered and analyzed using SPSS 22. Results: In our study 167 patients were enrolled with mean age of 37.52±16.6 years, minimum age was 12 years and maximum age was 37.52 years. There were 24% (40) male patients and 76% (127) were female patients. Mean duration of HCQ use was 2.34±0.88 years. Most common adverse effects noted in our study was dermatological manifestations including skin hyperpigmentation in 28.1% (47) patients followed by urticarial rash in 13.8% (23), second most common involved system was gastrointestinal system including nausea in 10.8% (18), diarrhea in 9% (15), headache in 9.6% (16), heart blocks were observed in 8.4% (14) patients least common adverse effects included were myopathy in 7.2% (12) and retinal toxicity in 3.6% (6) patients only. Conclusion: Cutaneous and gastrointestinal symptoms are most commonly reported adverse effected by HCQ when used in patients of autoimmune disease.